The trauma and acute care surgeon in the COVID-19 pandemic era (SciELO Preprints, 2020)
The World Health Organization recognized in March 2020 the existence of a pandemic for the new coronavirus that appeared in China, in late 2019, and whose disease was named COVID-19. In this context, the SBAIT (Brazilian Society of Integrated Care for Traumatized Patients) conducted a survey with 219 trauma and emergency surgeons regarding the availability of personal protective equipment (PPE) and the role of the surgeon in this pandemic by means of an electronic survey. It was observed that surgeons have been acting under inadequate conditions, with a lack of basic supplies as well as more specific equipment such as N95 masks and facial shields for the care of potential victims who may be contaminated. The latter increases the risk of contamination of professionals, resulting in potential losses in the working teams. Immediate measures must be taken to guarantee access to safety equipment throughout the country, since all trauma victims and/or patients with emergency surgical conditions must be treated as potential carriers of COVID-19.